Microbes trading electricity in consortia of environmental and biotechnological significance. (February 2021) - Rotaru, Amelia-Elena; Yee, Mon Oo; Musat, Florin
Abstract : Favorable interspecies associations prevail in natural microbial assemblages. Some of these favorable associations are co-metabolic dependent partnerships in which extracellular electrons are exchanged between species. For such electron exchange to occur, the cells must exhibit electroactive interfaces and get involved in direct cell-to-cell contact (D irect I nterspecies E lectron T ransfer/DIET ) or use available conductive mineral grains from their environment (C onductive-particle-mediated I nterspecies E lectron T ransfer/CIET ). This review will highlight recent discoveries and knowledge gaps regarding DIET and CIET interspecies associations in artificial co-cultures and consortia from natural and man-made environments and emphasize approaches to validate DIET and CIET. Additionally, we acknowledge the initiation of a movement towards applying electric syntrophies in biotechnology, bioremediation and geoengineering for natural attenuation of toxic compounds. Next, we have highlighted the urgent research needs that must be met to develop such technologies.